(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تم في سورية إصدار حزمة من التشريعات والقوانين التي تعنى بتأمين البيئة الاقتصادية والقانونية والمالية اللازمة لانطلاق عمل قطاع الأعمال. إن التطور المهم الذي طرأ على بيئة الأعمال في سورية، لم يؤدِ إلى استجابة هذا القطاع بالدرجة نفسها لجهة تطوير أنظمته المحاسبية وفق المعايير الحديثة وإنتاج المعلومات المحاسبية الملائمة، بحيث يجعل من معظم تلك المعلومات قاعدة غير صالحة للوفاء بمتطلبات اقتصاد السوق الاجتماعي الذي تم تبنيه رسمياً في المؤتمر القطري العاشر لحزب البعث العربي الاشتراكي في حزيران 2005. يحاول هذا البحث من خلال الاعتماد على منهج وصفي تحليلي دراسة وتحليل مختلف العوامل في بيئة الاقتصاد السوري بهدف تحديد أهم الأسباب التي تحول دون إحداث التطوير المرغوب على مستوى هذه النظم، ووضع بعض التصورات التي قد تشكل مدخلاً لإحداث هذا التطوير في ضوء المتطلبات المذكورة. وتشير نتائج البحث إلى أن قطاع الأعمال يفتقر إلى نظم معلومات محاسبية ملائمة, إذ يقتصر الموجود منها على تطبيق بعض المبادئ المحاسبية المتعارف عليها, بالإضافة إلى عدم مساهمة الجهات الرسمية بدور فاعل في تكوين هذه النظم, الأمر الذي يؤكد تدني مستوى مهنتي المحاسبة والمراجعة والافتقار إلى الموارد البشرية ذات الكفاءة. Many legislations and laws have been issued recently in Syria in order to provide the necessary economic, legislative and financial environment to launch the business sector. The significant development that occurred in the business environment in Syria, however, did not lead to similar development in respect of developing the accounting systems in this sector to fit with international accounting standards and the need to produce relevant accounting information. This makes most of this information unsuitable base to fulfill the requirements of the Social Market Economy, which was adopted officially in Syria in the 10th National Conference of the Socialist Arab Baath Party in June, 2005. This research examines and analyzes, through a descriptive analytical approach, the different factors in the environment of the Syrian economy that prevent the intended development of these systems. It also provides some ideas that may form an approach towards developing these systems in the light of the changes in Syrian business environment. Results of this research reveal that economic sector still lacks suitable accounting information systems, and that the existing systems use only some of the known accounting principles. Furthermore, the official bodies do not play an effective role in establishing these systems. It was found also that accounting and auditing professions are still not well developed and that there is a lack for qualified human resources.